Dietary total antioxidant capacity and the risk of developing asthenozoospermia: a hospital-based case–control study in China. Issue 4 (2nd February 2023) - Huang, Donghui; Zhang, Yixiao; Wang, Xiaobin; Guo, Renhao; Leng, Xu; Du, Qiang; Wu, Qijun; Pan, Bochen; Zhao, Yuhong
Abstract: STUDY QUESTION: Is dietary total antioxidant capacity (DTAC) associated with the odds of developing asthenozoospermia in Chinese men? SUMMARY ANSWER: There is no statistically significant association between DTAC indices and the odds of developing asthenozoospermia. WHAT IS KNOWN ALREADY: Both diet and oxidative stress may be related to sperm quality; however, few studies have investigated the association between DTAC and sperm quality. STUDY DESIGN, SIZE, DURATION: This case–control study was conducted from June 2020 to December 2020. Those diagnosed with asthenozoospermia were assigned to the case group, whereas those with normal sperm parameters were assigned to the control group. Data from a total of 553 cases and 586 controls were included in the final analysis. PARTICIPANTS/MATERIALS, SETTING, METHODS: Men who had been referred to the infertility clinic of Shengjing Hospital of China Medical University were enrolled. Dietary intake was assessed using a validated food frequency questionnaire. DTAC was based on ferric-reducing ability of plasma (FRAP), total oxygen radical absorbance capacity (T-ORAC), hydrophilic oxygen radical absorbance capacity (H-ORAC), lipophilic oxygen radical absorbance capacity (L-ORAC), total phenolics (TP), total radical-trapping antioxidant parameter (TRAP), and Trolox equivalent antioxidant capacity (TEAC). Asthenozoospermia was defined according to the criteria published in the fifth edition of the World Health Organization laboratory manual for the examination and processing of human semen. MAIN RESULTS AND THE ROLE OF CHANCE: No significant association was observed between the DTAC indices and the odds of asthenozoospermia after multivariable adjustment (T3 vs T1, odds ratio (OR) = 0.99, 95% CI: 0.73–1.33 for FRAP; OR = 1.05, 95% CI: 0.77–1.42 for T-ORAC; OR = 0.88, 95% CI: 0.65–1.18 for H-ORAC; OR = 0.98, 95% CI: 0.71–1.34 for L-ORAC; OR = 1.03, 95% CI: 0.76–1.39 for TP; OR = 1.18, 95% CI: 0.87–1.59 for TRAP; and OR = 1.15, 95% CI: 0.85–1.55 for TEAC). Both additive and multiplicative interaction analyses suggested that smoking might modify the association of T-ORAC with the odds of developing asthenozoospermia (relative excess risk due to interaction = 0.45, 95% CI: 0.07–0.83, attributable proportion due to interaction = 0.46, 95% CI: 0.07–0.84 for additive interaction; P  =   0.033 for multiplicative interaction). LIMITATIONS, REASONS FOR CAUTION: Recall bias and protopathic bias were inevitable in this retrospective case–control study. The estimation accuracy of the DTAC indices may have also affected the findings. WIDER IMPLICATIONS OF THE FINDINGS: To the best of our knowledge, this is the first study to specifically investigate whether an association exists between DTAC and the odds of developing asthenozoospermia. Although no significant association was found, this study provides novel information pertaining to the fields of nutrition and human reproduction. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the JieBangGuaShuai Project of Liaoning Province (2021JH1/10400050), the Shengjing Hospital Clinical Research Project (M0071), and the Outstanding Scientific Fund of Shengjing Hospital (M1150). All authors have no competing interests to disclose. TRIAL REGISTRATION NUMBER: N/A.